Penciptaan Hiasan Dinding Motif Sekar Jagad Sumatera Utara Dengan Teknik Batik Tulis - Mutiarani Mutiarani; Sri Wiratma (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The background to this creation is that traditional motifs no longer receive much attention from society. In North Sumatra, these motifs are rarely applied to the walls of office buildings and people's homes, especially in urban areas. Entering the modern era has resulted in people participating in following trends that are increasingly developing. This creation aims to find out the process of creating written batik works with the Sekar Jagad North Sumatra motif and to find out the results of creating written batik works with the Sekar Jagad North Sumatra motif. This creation uses a method consisting of five stages of creating works of art, namely: preparation, elaboration, synthesis, concept realization, and completion. The result of this creation is the batik wall decoration work of Sekar Jagad North Sumatra, consisting of 12 batik works. This written batik work uses the dabbing technique with remasol dye. North Sumatra motifs are used as the main motifs in written batik works by applying the Sekar Jagad batik pattern.